Body builder: from synthetic cells to engineered tissues. (October 2018) - Hu, Shiqi; Ogle, Brenda M; Cheng, Ke
Abstract : It is estimated that 18 Americans die every day waiting for an organ donation. And even if a patient receives the organ that s/he needs, there is still >10% chance that the new organ will not work. The field of tissue engineering and regenerative medicine aims to actively use a patient's own cells, plus biomaterials and factors, to grow specific tissues for replacement or to restore normal functions of that organ, which would eliminate the need for donors and the risk of alloimmune rejection. In this review, we summarized recent advances in fabricating synthetic cells, with a specific focus on their application to cardiac regenerative medicine and tissue engineering. At the end, we pointed to challenges and future directions for the field.